Relaksasi Otot Progresif terhadap Tekanan Darah Pasca Histerektomi pada Lansia - Siti Retnowati Yunita; Lisda Maria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of progressive muscle relaxation on blood pressure after hysterectomy in the elderly. This research method uses quantitative research with a quasi-experimental design with a pre-post test approach with a control group. The results showed a decrease in blood pressure of 29.2 mmHg in systolic blood pressure and 16.2 mmHg in diastolic blood pressure (p-value = 0.000; α = 0.05). In conclusion, progressive muscle relaxation effectively reduces blood pressure in post-hysterectomy elderly patients. Keywords: Hypertension, Elderly, Progressive Muscle Relaxation